2010
DOI: 10.1590/s1414-81452010000300007
|View full text |Cite
|
Sign up to set email alerts
|

Os sentimentos das mulheres pós-mastectomizadas

Abstract: RESUMOMichelly Gomes da Silva 2 Pesquisa qualitativa, que objetivou: descrever os sentimentos das mulheres sobre o câncer de mama e discutir as mudanças ocorridas na vida da mulher após o câncer de mama. Ocorreu em um ambulatório de ginecologia de um hospital público de Teresina. Foram entrevistadas 13 mulheres mastectomizadas. Na análise das entrevistas, surgiram três categorias: Sentimentos negativos gerados pela percepção física após mastectomia; Sentimentos positivos gerados pelo conforto espiritual; e Sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
31

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 10 publications
0
9
0
31
Order By: Relevance
“…9, No. 5;2017 assessment that even five years after surgery, sexual life does not return to normal (Moura, Silva, & Oliveira, 2010). However, according to a study of 135 women conducted in São Paulo, half of the women experienced a return to sexual activity within six months after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…9, No. 5;2017 assessment that even five years after surgery, sexual life does not return to normal (Moura, Silva, & Oliveira, 2010). However, according to a study of 135 women conducted in São Paulo, half of the women experienced a return to sexual activity within six months after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…16 The Collective Subject Discourse 02 showed that other elements are linked to the subjective suffering, since there is the emergence of concern caused by the detachment of the children, the husband and her home to carry out the treatment of cancer, since the city of residence there is not a reference hospital for cancer treatment. Often a woman is faced with a difficult situation for not having family support in the city of treatment affecting their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…A difícil aceitação e superação da nova condição da sexualidade traz uma relação direta com sentimentos desconhecidos. A depressão ou o aparecimento de sentimentos negativos na mulher mastectomizada torna-se mais frequente no pós-mastectomia 18 . Em um estudo feito com 13 mulheres pós mastectomia em hospital de referência em Teresina, cidade do Piauí, Brasil, foi relatado que as entrevistadas apresentavam sentimentos de medo, acanhamento, estranheza, tristeza, espanto e desânimo, ou seja, de desolação em relação à situação de mutilação a que foram submetidas, sendo que o choque existente em relação à percepção física é mais evidente após a visualização do resultado da mastectomia 18 .…”
Section: Figura 1: Autoexame Das Mamasunclassified